2004
DOI: 10.1109/tmm.2003.822795
|View full text |Cite
|
Sign up to set email alerts
|

Streaming Video Over Variable Bit-Rate Wireless Channels

Abstract: We consider streaming of video sequences over both constant and variable bit-rate (VBR) channels. Our goal is to enable decoding of each video unit before exceeding its displaying deadline and, hence, to guarantee successful sequence presentation even if the media rate does not match the channel rate. In this work, we will show that the separation between a delay jitter buffer and a decoder buffer is in general suboptimal for VBR video transmitted over VBR channels. We will specify the minimum initial delay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 9 publications
0
66
0
Order By: Relevance
“…Jitter in a streaming system [29] is avoided by having a delay jitter buffer at the receiver placed before the video decoding buffer that compensates for channel and traffic arrival variations. However, [30] showed that a single receiver buffer is sufficient to achieve a certain QoS guarantee. It can be seen from our experiments that the jitter after using variable bucket size network coding improves by 70% when compared with only TCP and by 60% when compared with TCP and fixed size network coding.…”
Section: Discussionmentioning
confidence: 99%
“…Jitter in a streaming system [29] is avoided by having a delay jitter buffer at the receiver placed before the video decoding buffer that compensates for channel and traffic arrival variations. However, [30] showed that a single receiver buffer is sufficient to achieve a certain QoS guarantee. It can be seen from our experiments that the jitter after using variable bucket size network coding improves by 70% when compared with only TCP and by 60% when compared with TCP and fixed size network coding.…”
Section: Discussionmentioning
confidence: 99%
“…By this the problems related to buffer adoption and delay bounds with data rate have been extracted. Admission Control for Statistical QoS proposed by Shroff et al [16] in which a buffer-less multiplexer introduces and they conclude economics of scale in the number of multiplexed flows was a crucial component in achieving a high degree of accuracy. They also experimentally observed loss curves (loss probability vs. buffer size).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The equation (15) means that the probability of no starvation is 1 conditioned by i ≥ 1 and n = 1. Thus, the probability of having one or more starvations is 0 obviously if the only packet sees a nonempty system.…”
Section: B Pgf Of Starvationsmentioning
confidence: 99%